Implementasi Kegiatan Bermain Huruf dalam Melatih Kemampuan Literasi Membaca Dasar Anak Usia Dini - Purnamasari, Nia Indah; Rohmawati, Heni (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2023)
The initial effort to strengthen literacy was to train young children in reading activities. By strengthening reading literacy in early childhood, we not only teach reading but also understand its meaning as a window to the world. This is intended to build a foundation for young children so that they are better prepared when they learn to actually read in the future. This research aims to analyze the implementation of letter game activities in training basic reading literacy skills of early childhood in group A at RA Muslimat Nurul Islam II, Suko Village, Sukodono District, Sidoarjo Regency. This research is qualitative descriptive research. The research results show that reading literacy skills will get optimal results with educational, innovative and fun game activities. So that children feel that learning is fun, not stressful. Through the medium of the letter circle speed game and letter cards the enthusiasm and enthusiasm of the students can be seen. Letter game activities carried out gradually and continuously will teach young children the concept of fun reading literacy. The author recommends encouraging students to play an active role by conveying ideas, imagination and thoughts during the learning process in order to get optimal results. Apart from that, educators should be creative and innovative in creating learning activities and consistent in carrying out literacy habits for every play activity.